Financial fragility and natural disasters: An empirical analysis - Klomp, Jeroen (Journal of Financial Stability, 2014)
Using data for more than 160 countries in the period 1997–2010, we explore the impact of large-scale natural disasters on the distance-to-default of commercial banks. The financial consequences of natural catastrophes may stress and threaten the existence of a bank by adversely affecting their solvency. After extensive testing for the sensitivity of the results, our main findings suggest that natural disasters increase the likelihood of a banks’ default. More precisely, we conclude that geophysical and meteorological disasters reduce the distance-to-default the most due to their widespread damage caused. In addition, the impact of a natural disaster depends on the size and scope of the catastrophe, the rigorousness of financial regulation and supervision, and the level of financial and economic development of a particular country.